Análise de desempenho de lagoas de estabilização empregadas para tratamento de lixiviados de aterros sanitários - Alice Libânia Santana Dias (2012)
Treating the landfill leachate has been proved to be a challenge to sanitation professionals. The international literature reports the need to complement the pre-existing biological method using chemical and physical methods in order to treat leachate. However, in Brazil, environmental agencies permit this treatment to be done exclusively biologically which is, in a certain way, contradictory once the legal Brazilian stringent requirements for wastewater treatment establish it should be done according to high standards. This research is about the performance of the stabilization ponds, which have been used to treat landfill leachate in Minas Gerais. Primary and secondary data were used focusing on the physical/chemical and biological parameters of raw and treated leachate. The primary data present COD levels from 164 to 21.137 mg/L, and efficiency removal rate from 3 to 97%. The values of ammonium nitrogen found in the raw leachate were from 21 to 2.808mg/L, with efficiency removal rate from 0 to 99%. Even in those systems which had a good efficiency removal rate in terms of BOD and COD, the values observed in the leachate treatment plants are still high considering the parameters of total suspended solids, COD, conductivity and ammonium nitrogen which prove the need to have more phases added to the treatment. The leachate treatment plant in the oldest landfill presented low efficiency rates when compared to the others. In this plant, the COD removal rates were average, 64%, and the remaining treated COD highest rate was of 3792mg/L; the ammonium nitrogen removal rate was of 85%, and its remaining portion was treated up to 360mg/L; the treated leachate COD/BOD rates were high, up to 0,49, which demonstrates that there are still some biodegradable organic materials. Among the 32 landfills still in use in the State during the period of analysis, 6 of them (19%) send their leachate to a combined treatment with domestic sewage in a municipal sewage treatment plan, two of them use an alternative type of treatment, and the other 24 (75%) have stabilization ponds in their facilities. Nevertheless, 17 of these leachate treatment plants do not present downstream flow and for that reason there is no start up from the treatment plant. In spite of having the infrastructure and the license to be stabilization ponds, they are functioning as leachate accumulation and evaporation systems. This operation presents environmental impacts which should be assessed along with measures that should be studied and put in practice to minimize this impact.